2017
DOI: 10.1016/j.lwt.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative vinification assays with selected Patagonian strains of Oenococcus oeni and Lactobacillus plantarum

Abstract: The performance of Patagonian Lactobacillus plantarum and Oenococcus oeni strains as malolactic starter cultures was compared. Two autochthonous strains of each species were selected, based on the presence of aroma-related genes, and inoculated in sterile wine of high ethanol content. The effects of initial inoculum size and pre-acclimation treatment on the efficiency of malolactic fermentation (MLF) were analyzed for each strain. O. oeni strains were able to successfully conduct the MLF only when the inoculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…In contrast, both strains showed higher tolerance to Pinot noir wine conditions, exhibiting a lower decrease of cell survival, but showing significant differences between the two cultures media employed. Cultures from MRS showed similar results than previously reported by our group, where an acclimation treatment was mandatory for a successful consumption of L‐malic acid in Pinot noir wine . Interestingly, cultures from WPYST showed higher %MAC, for both strains; where UNQLp11 had a better performance since it was able to deplete the L‐malic acid content after 21 days.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In contrast, both strains showed higher tolerance to Pinot noir wine conditions, exhibiting a lower decrease of cell survival, but showing significant differences between the two cultures media employed. Cultures from MRS showed similar results than previously reported by our group, where an acclimation treatment was mandatory for a successful consumption of L‐malic acid in Pinot noir wine . Interestingly, cultures from WPYST showed higher %MAC, for both strains; where UNQLp11 had a better performance since it was able to deplete the L‐malic acid content after 21 days.…”
Section: Discussionsupporting
confidence: 82%
“…Although the ethanol content in this wine (12.2% vol/vol) was lower than in Pinot noir (14.3% vol/vol), its pH was also lower (3.45) and this could be the cause of the different performances . It is also important to note that the strains assayed were isolated from Pinot noir wine samples …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculated acetaldehydes produced in samples with L. plantarum strains could effectively reduce the oxidative stress and thus delayed the oxidation of β-ionone. Additionally, O. oeni strains have been reported to release β-glucosidase, and this enzyme could hydrolyze the precursor of linalool and α-terpineol to yield these two terpene derivatives in wine malolactic fermentation [4,32,33,[80][81][82][83]. In the present study, a significant accumulation of linalool and α-terpineol was observed in the samples with O. oeni strains ( Table 3).…”
Section: Terpene Derivativesmentioning
confidence: 50%